ESPOR game changing technology for Sports (2012)
Every sport can be broken down by the numbers - the statistical data that make up the action within each game. By combining video with these statistics, you can see both the numbers and the action as they relate to one another. Data points on the field or court create location tracking, giving you the ability to see tendency reporting, statistical breakdowns and graphic reporting together. We call this true game analysis and it is what each of our pro line of products is designed to do.